Primary ovarian insufficiency: a glimpse into the racial and socioeconomic disparities found within third-party reproduction - Ashley Wiltshire, M.D; Luwam Ghidei, M.D; Josette Dawkins, M.D; Kiwita Phillips, M.D; Frederick Licciardi, M.D; David Keefe, M.D (Elsevier, 2022)
Objective: To describe a unique case of primary ovarian insufficiency and review the systemic barriers in place that hinder reproductive autonomy for Black women who require third-party reproduction. Design: Case report and review of the literature. Setting: Safety-net hospital in an urban community. Patient(s): A 36-year-old Black woman, gravida 0, with primary ovarian insufficiency who desires future fertility but is restricted by systemic barriers. Intervention(s): Chromosome analysis. Main Outcome Measure(s): Not applicable. Result(s): Balanced reciprocal translocation between chromosomes 1 and 13: 46,XX,t(1;13)(q25;q14.1). Conclusion(s): The field of assisted reproductive technology has evolved at an exponential rate, yet it unfortunately benefits some and not all. It is imperative that when we advocate for full spectrum infertility care, that this encompasses everyone. As we continue to further study and develop assisted reproductive technology, we must not forget to consider the factors leading to racial and socioeconomic disparities in reproductive care access, utilization, and outcomes.